Test for Determination of Tannin Characteristics of Oolong Tea Leaf Extract (Camellia sinensis (L.) Kuntze) from Kemuning Tea Plant Karanganyar - Styawan, Anita Agustina; Khairiyah, Fatikhatun Nissa’ (Journal of Food and Pharmaceutical Sciences, 2025)
The oolong tea plant protects the body's cells from the damaging effects of free radicals by acting as an antioxidant. The content of oolong tea leaves contains tannin compounds which have a good effect on the body and the more tannin content in the tea, the greater it is its antioxidant activity. The purpose of this study is to use UV-visible spectrophotometry to ascertain the tannin content of the oolong tea leaf extract from the Kemuning tea plantation. The observational research method is being used. A sample of dried oolong tea leaves is used in this investigation. 1% FeCl3 was used to assess the sample qualitatively, and UV-Vis spectrophotometry was used to analyze the sample quantitatively. The solvent used was ethanol 96%%. The study's conclusions show that the sample contains tannins, which are qualitatively distinguished by a shift in color to a greenish-black tint. The oolong tea leaf extract has a quantifiable tannin concentration of 12.26% mg TE/g. Indicates that tannins can give a bitter and astringent taste, and can give a pleasant flavor to tea.